The Road Less Taken: Less Appreciated Pathways for Manipulating CD8+ T Cell Exhaustion - Pichler, Andrea C.; Cannons, Jennifer L.; Schwartzberg, Pamela L. (Frontiers in Immunology, 2022)
Exhausted CD8+ T (Tex) cells are a distinct cell population that arise during persistent antigen exposure in the context of chronic infections and cancers. Although characterized by progressive loss of effector functions, high and sustained inhibitory receptor expression and distinct transcriptional and epigenetic programs, Tex cells are heterogeneous. Among these, a self-renewing TCF-1+ Tex population, having unique characteristics and the ability to respond to immune-checkpoint blockade, gives rise to TCF-1- terminal Tex cells. These TCF-1+ cells have stem cell-like properties similar to memory T cell populations, but the signals that regulate the developmental pathways and relationships among exhausted cell populations are still unclear. Here, we review some or our current understanding of Tex cell biology, and discuss some less appreciated molecules and pathways affecting T cell exhaustion. We highlight two co-stimulatory receptors, CD226 and CD137, and their role in inducing or restraining T cell exhaustion, as well as signaling pathways that may be amenable to pharmacological inhibition with a focus on Phosphoinositide-3 Kinase and IL-2. Finally, we discuss novel methods that may increase TCF-1+ populations and therefore improve immunotherapy responsiveness. Understanding features of and pathways to exhaustion has important implications for the success of immunotherapy, including checkpoint blockade and adoptive T-cell transfer therapies.